Johannesson, Nils-Lennart, and Andrew Cooper, eds. 2023. The Ormulum. 2 vols. Oxford: Oxford University Press. Pp. xxviii + 655. ISBN 9780192890436. - van Baalen, Amos (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Johannesson, Nils-Lennart, and Andrew Cooper, eds. 2023. The Ormulum. 2 vols. Oxford: Oxford University Press. Pp. xxviii + 655. ISBN 9780192890436.